Mental health and wellbeing of jockeys - Losty, C.; Warrington, G.; McGoldrick, A.; Murphy, C.; Burrows, E.; Cullen, S. J. (Journal of Human Sport & Exercise, 2019)
Despite receiving much public attention in recent years, the mental health status of jockeys has not been established. This study investigated the incidence of common mental health disorders in jockeys. Amateur (n=74) and professional (n=42) jockeys completed an online anonymous questionnaire incorporating validated self-reported measurement tools to assess the prevalence of psychological distress, depression, anxiety, social phobia, perceived stress and self-esteem. Personal and lifestyle characteristics were also reported. Fifty four percent of jockeys were experiencing symptoms of at least one of general psychological distress, depression, general anxiety disorder or social anxiety. Professional jockeys displayed significantly greater mean scores on measures of psychological distress (p<0.01), depression (p<0.05), anxiety (p<0.05) and perceived stress (p<0.01). No difference was present in measures between professional flat and jump jockeys. Professional jockeys were classified as displaying symptoms of depression (mean score 20.29; 57.1% at or above threshold of 16) and perceived stress (mean score 20.24; 52.4% at or above threshold of 20). Current injury, social anxiety or high levels of perceived stress increased the likelihood of displaying depressive symptoms in the jockey sample. With a high prevalence of depression and perceived stress evident in professional jockeys, mental health support strategies should be implemented with specific focus on stress management and dealing with injury. Future research should further investigate factors that increase the susceptibility of jockeys to mental health disorders.